Prevalence, Epidemiological Characteristics, and Pharmacotherapy of Coronary Artery Disease among Patients with Atrial Fibrillation: Data from Jo-Fib Study - Hanna K. Al-Makhamreh; Mohammed Q. Al-Sabbagh; Ala’ E. Shaban; Abdelrahman F. Obiedat; Ayman J. Hammoudeh (Medicina, 2021)
Background and Objectives: Patients with AF are at increased risk for Coronary Artery Disease (CAD) owing to their shared etiologies and risk factors. This study aimed to assess the prevalence, cardiovascular risk factors, and used medications of CAD in AF patients. Materials and Methods: This retrospective, case-control study utilized data from the Jordanian Atrial Fibrillation (Jo-Fib) registry. Investigators collected clinical features, history of co-existing comorbidities, CHA2DS2-VASc, and HAS BLED scores for all AF patients aged >18 visiting 19 hospitals and 30 outpatient cardiology clinics. A multivariable binary logistic regression was used to asses for factors associated with higher odds of having CAD. Results: Out of 2000 patients with AF, 227 (11.35%) had CAD. Compared to the rest of the sample, those with CAD had significantly higher prevalence of hypertension (82.38%; p < 0.01), hypercholesterolemia (66.52%, p < 0.01), diabetes (56.83%, p < 0.01), and smoking (18.06%, p = 0.04). Patients with AF and CAD had higher use of anticoagulants/antiplatelet agents combination (p < 0.01) compared to the rest of the sample. Females had lower CAD risk than males (OR = 0.35, 95% CI: 0.24–0.50). AF Patients with dyslipidemia (OR = 2.5, 95% CI: 1.8–3.4), smoking (OR = 1.7, 95% CI: 1.1–2.6), higher CHA2DS2-VASc score (OR = 1.5, 95% CI: 1.4–1.7), and asymptomatic AF (OR = 1.9, 95% CI: 1.3–2.6) had higher risk for CAD. Conclusions: Owing to the increased prevalence of CAD in patients with AF, better control of cardiac risk factors is recommended for this special group. Future studies should investigate such interesting relationships to stratify CAD risk in AF patients. We believe that this study adds valuable information regarding the prevalence, epidemiological characteristics, and pharmacotherapy of CAD in patients with AF.